A note on the locus and function of formal gender - Picallo, M. Carme (Borealis – An International Journal of Hispanic Linguistics, 2017)
This paper examines some aspects of nominal inflection. It focuses in particular on noun classification with evidence drawn mainly from Spanish where noun classification surfaces as formal Gender. Under a minimalist lens, this feature is a puzzling grammatical element because it seems uncongenial to the idea of optimal design. I examine some syntactic evidence to assess the syntactic locus of Gender features in nominal structures, and conjecture that noun classification simply externalizes some basic properties of the linguistic system in the functional domain. I motivate my conclusions on the basis of empirical evidence and recent theoretical proposals that argue for the adoption of a much more abstract conception of syntactic constructs than those we have generally been considering.